2011
DOI: 10.1002/lt.22209
|View full text |Cite
|
Sign up to set email alerts
|

Digital image analysis of liver collagen predicts clinical outcome of recurrent hepatitis C Virus 1 year after liver transplantation

Abstract: Clinical outcomes of recurrent hepatitis C virus after liver transplantation are difficult to predict. We evaluated collagen proportionate area (CPA), a quantitative histological index, at 1 year with respect to the first episode of clinical decompensation. Patients with biopsies at 1 year after liver transplantation were evaluated by Ishak stage/grade, and biopsy samples stained with Sirius red for digital image analysis were evaluated for CPA. Cox regression was used to evaluate variables associated with fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 55 publications
2
65
0
Order By: Relevance
“…In previous studies, CPA in recurrent HCV post-LT correlated with both Ishak stage scores and HVPG, with greater percentage changes in CPA than in HVPG in early portal hypertension [6]. CPA at 1-year biopsy post-LT for HCV cirrhosis was highly predictive of clinical outcome and better than Ishak stage or HVPG [7]. Lastly, CPA allows subclassification of cirrhosis [8] and this potentially increases the possibility of using histological parameters in cirrhosis to predict clinical outcomes.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In previous studies, CPA in recurrent HCV post-LT correlated with both Ishak stage scores and HVPG, with greater percentage changes in CPA than in HVPG in early portal hypertension [6]. CPA at 1-year biopsy post-LT for HCV cirrhosis was highly predictive of clinical outcome and better than Ishak stage or HVPG [7]. Lastly, CPA allows subclassification of cirrhosis [8] and this potentially increases the possibility of using histological parameters in cirrhosis to predict clinical outcomes.…”
Section: Introductionmentioning
confidence: 71%
“…CPA at one time point is a histological measurement that quantifies fibrosis, and relates to clinical outcomes [6,7]. CPA also correlates with HVPG with wider range of values in patients with Ishak stage 5/6, showing that cirrhosis can be subclassified [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers are not arithmetically proportionate, i.e., stage 2 is not half of stage 4 (19,20). The need for an objective method, has led to the increasing use of digital image analysis (DIA) technology with collagen quantification using collagen proportionate area (CPA) for liver fibrosis assessment (21)(22)(23)(24)(25). As the number of hepatocytes decreases with increasing number of collagen deposition, the functional reserve is diminished accordingly (26).…”
Section: Liver Biopsymentioning
confidence: 99%
“…They also reported that CPA at 1-year post-transplantation in hepatitis C virus-infected patients predicts subsequent clinical decompensation more accurately than Ishak stage or HVPG [5]. They conclude that CPA should be the histological parameter with which to compare LSM and other non-invasive fibrosis markers and also be used to subclassify cirrhosis.…”
mentioning
confidence: 97%